High pressure-assisted low-loading asymmetric organocatalytic conjugate addition of nitroalkanes to chalcones12. Issue 23 (31st May 2018) - Cholewiak, Agnieszka; Adamczyk, Kamil; Kopyt, Michał; Kasztelan, Adrian; Kwiatkowski, Piotr
Abstract : A highly enantioselective and relatively fast (1–5 h) Michael reaction with substantial reduction of organocatalyst loading (0.2–1 mol%) was developed under high-pressure conditions (up to 9 kbar) and at room temperature. Abstract : The application of high pressure (up to 9 kbar) allows for relatively fast (1–5 h) and highly enantioselective 1, 4-addition of nitromethane and 2-nitropropane to chalcones at room temperature with substantial reduction of catalyst loading (0.2–1 mol% of cinchona alkaloid-based thioureas and squaramides). Various γ-nitroketones were obtained at 9 kbar with high yield and enantioselectivity (up to 98%), whereas in control experiments at atmospheric pressure usually only a small amount (<10%) of products were formed after 20 h.